Dampak Keruntuhan Jembatan Lempuyang Pada Jalan Lintas Timur dan Lintas Penghubung Provinsi Lampung - Permani, Ratih Diah; Hadi, Yohanes Martono; Adha, Idharmahadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
The Indonesian Transportation System, which is still dominated by ground transportation, has made the road have a more dominant role in economic growth. The condition of road facilities and infrastructure also encourages economic growth among regions connected by infrastructure networks, so that it is expected that in various regions there will be equitable growth.The collapse of the Lempuyang bridge resulted in a change in the volume of traffic flow on the roads that became an alternative road. This volume change can directly affect the condition of the road designated as an alternative road, namely the eastern crossroad (Sukadana - Sp. Bujung Tenuk) and the Tegineneng Feeder - Sukadana road.The segment most affected by the damage to the Lempuyang bridge is the Central - Metro - Sukadana feeder segment. In the Central - Metro - Sukadana feeder there was an increase in the size of the slightly damaged  road  in May 2015 from  2014, from 2.52% to 9.03%. The value of severely damaged conditions in the Central - Metro - Sukadana feeder also increased where in 2014 it was worth 0.00% to 5.34% in May 2015. Keywords: East Cross Road, Lempuyang Bridge, Road Condition Value